Retrospective analysis of clinical and laboratory findings of children with rotavirus gastroenteritis in Malatya province between 2015 and 2020 (Annals of Medical Research, 2023)
Aim: In the present study, our aim was to examine cases with rotavirus gastroenteritis, which is an important health problem, in detail.Materials and Methods: Cases with acute gastroenteritis aged between 0 and 18 who referred to Inonu University Turgut Ozal Medical Centre between January 2015 and January 2020 and whose stools were examined for rotavirus antigen were included in the study. The cases who were grouped in two as “rotavirus positive and rotavirus negative gastroenteritis” were examined retrospectively in detail in terms of their states of being followed and treated as outpatient, inpatient and in intensive care.Results: A total of 2690 children, 1340 rotavirus positive and 1350 rotavirus negative control group were included in the study. Rotavirus positive gastroenteritis was most common in winter (27.2%). 53.9% of the rotavirus positive gastroenteritis cases were followed and treated as inpatients. In rotavirus positive patients, mean age of the inpatients was 3.3±4.2 years, while mean age of the outpatients was 2.1±3.1 years and mean age of the patients in the intensive unit care was 1.6±3.2 years. The highest rates of rotavirus positive gastroenteritis cases were in 7-12 month old (19.8%), 13-24 month old (23.9%) and 25-60 month old (24.1%) age groups, while the lowest rates were in 0-2 month old (3.1%) and 3-6 month old (10.2%) age groups.Conclusion: In our study, the lowest rate of rotavirus positive gastroenteritis cases was found in 0-2 month-old age group. It was thought that this situation might be due to the significant effect of antibodies transmitted transplacentally from the mother, especially between months 0 and 2. The increase in rotavirus positivity and hospitalization after the sixth month showed the importance of administering the rotavirus vaccine before this period once again.
Keywords: Child; Gastroenteritis; Laboratory; Malatya; Rotavirus